1153 SODIUM GLUCOSE COTRANSPORTER-2 INHIBITORS ELIGIBILITY IN PATIENTS WITH HEART FAILURE ACROSS THE SPECTRUM OF EJECTION FRACTION. (15th December 2022) - Ferrari, Ilaria; Monzo, Luca
Abstract: Background: Large randomized clinical trials demonstrated that sodium–glucose co-transporter-2 (SGLT2) inhibitors reduced adverse cardiovascular outcomes in patients with heart failure (HF) with both reduced (HFrEF) and preserved (HFpEF) ejection fraction. Despite the high potential to change clinical practice, the strict trial selection criteria might reduce external validity of these findings. Purpose: The aim of the study was to evaluate the proportion of outpatients with HF that would be eligible for SGLT2 inhibitors across the spectrum of left ventricular ejection fraction (LVEF) in a contemporary real-world population. Methods: We retrospectively evaluated patients with chronic stable HF followed-up at the outpatient clinic of our institution. HFrEF (LVEF <40%) patients' eligibility was assessed according to the entry criteria of DAPA-HF (dapagliflozin) and EMPEROR-Reduced (empagliflozin) trials and to US Food and Drug Administration (FDA) label criteria (only dapagliflozin). In HFpEF group (LVEF>40%), Eligibility to SGLT2 inhibitors was based both strict and pragmatic (most likely influencing treatment decisions in clinical practice) EMPEROR- Preserved inclusion/exclusion criteria (empagliflozin). Results: A total of 642 HF patients (441 HFrEF; 201 HFpEF) was studied. Among HFrEF patients, according to the major inclusion and exclusion criteria from DAPA-HF and EMPEROR-Reduced trials, 198 (45%) patients would be candidates for initiation of both dapagliflozin and empagliflozin, 61 (14%) would be eligible only to dapagliflozin and 23 (5%) only to empagliflozin, On the other hand, in HFpEF patients, 125 (62%) patients would be candidates for initiation of empagliflozin based on the EMPEROR-Preserved trial selection criteria. No significant differences were found between diabetic and non-diabetic patients in both HFrEF (p=0.23) and HFpEF (p=0.37). In patients not suitable for gliflozins treatment the major determinant of ineligibility was the failure to achieve the predefined NTproBNP inclusion threshold. Excluding NTproBNP as per FDA label criteria, dapagliflozin eligibility increased to 86%. Similarly, applying EMPEROR-Preserved criteria most likely influencing treatment decisions in clinical practice (symptomatic HF; eGFR <20 mL/min/1.73 m2; symptomatic hypotension; history of ketoacidosis) the proportion of HFpEF patients potentially eligible to empagliflozin rose to 85%. Conclusions: In our real-world analysis the proportion of HF patients potentially candidate for initiation of SGLT2 inhibitors is consistent across the entire spectrum of LVEF. Our findings might herald an extensive use of gliflozins in HF treatment, with a consequent strong beneficial impact on cardiovascular outcomes in eligible patients.